Factors affecting the forest value chain resilience–a local economic perspective in five European countries - García-Jácome, Sandra Paola; Brudermann, Annechien; Stern, Tobias; Lindner, Marcus; Lloret, Francisco; Uzquiano, Sara; Asada, Raphael; Picos, Juan; Nuhlíček, Ondrej; Vuletić, Dijana; Peltoniemi, Mikko; Baumbach, Lukas; et al. (Frontiers in Forests and Global Change, 2025)
This study investigates the economic resilience of Forest Value Chains (FVC) at the local level through five European case studies: Kostelec, Czechia (CZ), Upper Rhine Valley, Germany (DE), Istria, Croatia (HR), Kainuu, Finland (FIN), and Galicia, Spain (ESP). Using an operational resilience framework (ORF) and a resilience assessment centered on revenue as a system variable. A sensitivity analysis of profitability thresholds confirmed the robustness of the results. Principal Component Analysis (PCA) was applied to examine market price fluctuations across various timber types, market trends and salvage logging practices from 2001 to 2021. Two-way fixed-effects panel regression models revealed that planned harvested volume, mechanization, and market prices were significant predictors of enhanced economic resilience. The analysis revealed three interrelated dimensions of FVC resilience: resistance to market shocks, recovery following disturbances, and capacity for transformation via adaptive management. Two predominant adaptation strategies emerged: a market-driven approach, characterized by product diversification and price stability, and a disturbance-driven strategy, focused on reactive harvesting and technological innovation. While salvage logging offered short-term economic relief, excessive dependence undermined long-term stability. The findings highlight the need to balance short-term recovery with long-term sustainability in managing Europe’s FVCs.